Análise dos acidentes de trânsito do Município de São Carlos utilizando o Sistema de Informação Geográfica - SIG e ferramentas de estatística espacial - Santos, Luciano dos (2006)
The traffic accidents have reached high records, registering a great amount of wounded and material damages. One of the largest concerns of the responsible organs for the planning of the traffic and transport is to find solutions that can come to reduce the numbers of traffic accidents. In this context, this work had as main objective to accomplish a spatial analysis of the accidents of traffic on the municipal district of São Carlos - SP, using a of Geographic Information System (GIS) associated to tools of Spatial Statistics, with the intention of identifying the points and areas of larger occurrence of accidents, as well as the spatial tendencies of growth. The work has been developed in two stages: a) determination of punctual patterns; and b) determination of critical zones. For the accomplishment of this work was necessary to make a geographic reference of the traffic accidents, happened between 2001 and 2003. The Spatial Statistics tools used in this work were the Index of Moran, Average Space Piece of furniture, among others; they were used for the accomplishment of groupings of traffic accidents, determination of the critical zones of accidents and the tendencies of displacement of the accidents. The work showed that the traffic accidents happen in all the mesh of urban way, with a larger incidence of accidents with material damages in the central areas of the city and accidents with victims in the outlying areas. It was possible to observe that a displacement of the accidents of traffic exists for almost all the areas of the São Carlos city, it being a spatial phenomenon of difficult treatment. The largest difficulty founded for the accomplishment of this work were linked to the analysis of the consistence of the information, it mean that the analyses of the traffic accidents will be each time more satisfactory, if we pay a larger attention in the collection process and storage of those information.